2015
DOI: 10.1002/ajmg.a.37190
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of psychiatric manifestations of 22q11.2 deletion syndrome in medical genetics: A 12‐year retrospective chart review

Abstract: Individuals with 22q11.2 deletion syndrome (22qDS) have increased risk for psychiatric disorders. However, while medical geneticists self-report discussing psychiatric features of 22qDS with families (though often only when the child is older), most parents of children with 22qDS report receiving information about the psychiatric manifestations of 22qDS from non-medical sources. In an attempt to reconcile these previous findings, we sought to objectively determine the frequency with which medical geneticists d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Concerns expressed about overloading parents with information in the aftermath of a genetic diagnosis need to be balanced against the best interests of children and their parents. 30,31 Consistent with earlier studies of rare chromosomal disorders, our findings also reveal that parents often consider information from clinical specialists to have lower practical value than material found online or obtained from support groups and is frequently too complicated or irrelevant. 32 Our findings reveal that patterns of information gathering differed between UK and US families.…”
Section: Discussionsupporting
confidence: 88%
“…Concerns expressed about overloading parents with information in the aftermath of a genetic diagnosis need to be balanced against the best interests of children and their parents. 30,31 Consistent with earlier studies of rare chromosomal disorders, our findings also reveal that parents often consider information from clinical specialists to have lower practical value than material found online or obtained from support groups and is frequently too complicated or irrelevant. 32 Our findings reveal that patterns of information gathering differed between UK and US families.…”
Section: Discussionsupporting
confidence: 88%
“…Our study showed that paediatric and genetic specialists tend to focus on providing information about developmental and physical disabilities at the time of giving genetic test results, suggesting either that information about psychiatric risks may be less readily available, or that informing parents about risks of behavioural, emotional and psychotic disorders is less relevant when communicating test results. [ 3133 ] In the context of communicating pathogenic neurodevelopmental CNVs with significant evidence of psychiatric, our findings indicated parents were no more likely to be informed about these than were others. Moreover, our findings suggest parents of children with ND-CNVs tend to find psychiatric information through alternative sources including internet searches, suggesting extensive evidence on neuropsychiatric genotype-phenotype associations in ND-CNVs is yet to be incorporated into genetic counselling for individuals with developmental disorders.…”
Section: Discussionmentioning
confidence: 85%
“…Although parents acknowledged there is good support around the physical, developmental, and cognitive issues their child may experience as a consequence of 22qDS, parents felt they missed guidance from their HCPs on MH. Previous studies have reported psychiatric disorders are discussed less often than the other features of 22qDS in a medical genetics setting (Morris et al., 2013; Martin et al., 2012; Talcott‐Baughman et al., 2015). Barriers, such as HCPs dealing with immediate symptoms, combined with the child's young age, provide potential explanations for the gap in MH information, resource, and support.…”
Section: Discussionmentioning
confidence: 98%
“…Psychiatric manifestations of the syndrome are known to be of considerable concern to parents of affected children, particularly the chance to develop a psychotic disorder like schizophrenia, which has been estimated at 25%–41%, as compared to a 3% general population risk for the same (Basset et al., 2003; Schneider et al., 2014). However, most parents report that they did not receive information about the psychiatric manifestations of 22qDS from a healthcare provider (Hercher & Bruenner, 2008), and indeed genetics professionals report discussing the psychiatric manifestations of 22qDS less often with families than other aspects of the condition (Martin et al., 2012; Morris et al., 2013; Talcott‐Baughman et al., 2015).…”
Section: Introductionmentioning
confidence: 99%